2010
DOI: 10.1063/1.3509778
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structures of gas-phase rhodium cluster cations by far-infrared spectroscopy

Abstract: The geometric structures of small cationic rhodium clusters Rh \documentclass[12pt]{minimal}\begin{document}$_n^+$\end{document}n+ (n = 6–12) are investigated by comparison of experimental far-infrared multiple photon dissociation spectra with spectra calculated using density functional theory. The clusters are found to favor structures based on octahedral and tetrahedral motifs for most of the sizes considered, in contrast to previous theoretical predictions that rhodium clusters should favor cubic motifs. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
104
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 63 publications
22
104
2
1
Order By: Relevance
“…This finding is consistent with recent screened hybrid-DFT calculations reported for Rh 13 , 27 which identified that an increase in the amount of exact Fock exchange in the hybrid functionals favors compact structures for Rh 13 , and hence, in better agreement with vibrational data. 24,25 However, it has been reported that low coordinated Rh n structures obtained by plain DFT calculations yield magnetic moments m T , in good agreement with experimental results. 10,[12][13][14][15][16] For example, plain DFT yields m T = 0.69 μ B /atom for Rh 13 , while results have obtained 0.48 ± 0.13 μ B /atom, 10 however, hybrid-DFT calculations yield higher magnetic moments for compact Rh n clusters (i.e., m T = 1.62 μ B /atom for Rh 13 ).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…This finding is consistent with recent screened hybrid-DFT calculations reported for Rh 13 , 27 which identified that an increase in the amount of exact Fock exchange in the hybrid functionals favors compact structures for Rh 13 , and hence, in better agreement with vibrational data. 24,25 However, it has been reported that low coordinated Rh n structures obtained by plain DFT calculations yield magnetic moments m T , in good agreement with experimental results. 10,[12][13][14][15][16] For example, plain DFT yields m T = 0.69 μ B /atom for Rh 13 , while results have obtained 0.48 ± 0.13 μ B /atom, 10 however, hybrid-DFT calculations yield higher magnetic moments for compact Rh n clusters (i.e., m T = 1.62 μ B /atom for Rh 13 ).…”
Section: Introductionsupporting
confidence: 75%
“…Thus, hybrid-DFT calculations yield compact structures and vibrational spectra in better agreement with experimental results, 24,25 however, the magnetic moments are too high compared with the experimental results. 10,27 In contrast, plain DFT yields open structures, which does not explain the vibrational spectra, 24,25 however, it yields total magnetic moments in excellent agreement with experimental results.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…A similar study, combining IR-MPD with BH-DFT calculations, was presented by Walsh and coworkers for Rh 1 N (N56212). [170,171] They observed a significant dependence of the most stable putative GM and its spin multiplicity on the functional, making the identification of the geometric and electronic GM very challenging. [170] These case studies illustrate the problems FP-GOs face when investigating transition metal clusters using DFT methods.…”
Section: Basin Hoppingmentioning
confidence: 99%
“…A better understanding of the nature of these fundamental interactions would inform fields as diverse as molecule surface interactions [1] and buffer gas cooling. [2] The study of such molecules has been lent added impetus in recent years, by the popular use of rare gas atoms as messenger tags in action spectroscopy studies of gas-phase metal-ligand [3,4] naked metal [5][6][7][8] and metal oxide clusters. [9][10][11] In such studies, the structures of interest are widely assumed to be affected minimally by the presence of the inert tag with the result that the photodissociation action spectrum mirrors that of the naked species.…”
Section: Introductionmentioning
confidence: 99%